Digital society: pathways towards health equity in advanced age - Bobrowicz-Campos, E. (Saúde societal no futuro Pós-covid -19. Resumos, 2022)
The growing trend of transferring essential services to the digital space requires from citizens to have digital literacy competences that are sufficient to access and critically use these services, so that they can benefit from digital innovation, without compromising their civic rights and obligations. The case of health services is particularly sensitive. The use of digital technologies in health can improve integrated and person-centred healthcare, bringing health services closer to citizens. However, in the absence of equipment or knowledge/skills or motivation that enable the goal-oriented and efficient use of these technologies, the access to healthcare may become limited, with this situation having serious implications for the citizens’ quality of life, well-being and health status. As such, efforts should be made to ensure that all citizens, regardless of age, gender, socio-economic status and place of residence, are able to use autonomously and effectively the technological tools that allow them to take advantage of services existing in the digital space. Take the example of adults in advanced age. According to the international reports, there are currently a large number of persons aged 65 years and over who, due to limited availability, accessibility and/or affordability of digital connectivity and infrastructure, are unable to take advantage from the digital and technological innovation, or even respond to their daily needs. Substantial gaps in digital literacy competences that limit the use of digital technologies to meet information, communication, leisure and entertainment needs have also been reported in this age group, as well as the reduced ability to benefit from the online commercial transactions and online interactions with the public authorities. These gaps have become especially visible in the times of pandemic, during which many adults in advanced age have been forced to struggle with a double burden of social and digital exclusion. On the other hand, the age group in question demonstrates a high demand for health services (e.g., in terms of consultation with general and surgical practitioners or need for medication to resolve their health problems and efficiently manage their long-standing illness), which is due to the aging-related decrease in homeostatic reserves in various physiological systems that boosts the risk of adverse health outcomes and leads to gradual loss of functional capacity and autonomy. For these citizens, close integrated and personalised healthcare is crucial to enable the efficient monitoring of their health status and the timely implementation of prevention and treatment approaches, thus contributing to reducing their vulnerability to health-related risks. In this perspective, it is necessary to ensure that those who have not yet embraced the digital and technological progress have opportunities to participate in actions that promote digital inclusion, as these actions may foster equitable access to health and prevent digitally illiterate or non-engaged citizens from being overlooked by decision-makers in the future.